Calibration Method for Active Element Patterns corrupted by the Parasitic Effects of Feeding Networks - Seongjung Kim (Journal of Electromagnetic Engineering and Science)
This paper presents a novel method for calibrating the active element patterns (AEPs) of array antennas distorted by feeding networks. These distortions include signal loss, multiple reflection, and parasitic radiation. This methodology is particularly relevant for millimeter-wave frequencies, at which feeding networks prominently impact antenna performance. The proposed approach utilizes the inherent consistency of vertical launch connectors, overcoming the issue of distortion and focusing on enhancing the accuracy and reliability of antenna performance measurements. Using an innovative calibration process, we demonstrate the ability to effectively correct distorted AEPs while simultaneously ensuring the fidelity of the antenna’s radiation pattern and reflection characteristics. The method’s effectiveness is validated through comparison with ideal simulated AEPs, showing significant improvement in radiation pattern characteristics, particularly at higher frequencies.